John C. Merriam papers - Merriam, John C. (John Campbell), 1869-1945.
Correspondence, memoranda, speeches, reports, articles, notes, printed matter, drawings, maps, photographs, and other papers relating chiefly to Merriam's work as chairman of the National Research Council (U.S.), president of the Carnegie Institution of Washington, and regent of the Smithsonian Institution. Also includes materials reflecting his interest in forestry and national parks. Correspondents include James Bertram, Henry Bryant Bigelow, Howard Walter Blakeslee, William DuBois Brookings, Ovid Butler, Ralph W. Chaney, Bruce L. Clark, Newton Bishop Drury, Charles W. Eliott, George Ellery Hale, Ansel F. Hall, Herbert Hoover, Edgar Billings Howard, Raymond M. Hughes, Vernon L. King, Frederick P. Keppel, Waldo Gifford Leland, Frank Rattray Lillie, Harold Glenn Moulton, Henry Fairfield Osborn, Earl L. Packard, Stewart Paton, Raymond Pearl, Elihu Root, L.S. Rowe, Chester Stock, William Charles White, Edwin Bidwell Wilson, F.E. Wright, Robert Sterling Yard, and Robert Mearns Yerkes.
Paleontologist, educator, and author.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Bertram, James, -- 1872-1934 -- Correspondence; Bigelow, Henry Bryant, -- 1879- -- Correspondence; Blakeslee, Howard Walter, -- 1880-1952 -- Correspondence; Brookings, William DuBois, -- 1873-1950 -- Correspondence; Butler, Ovid, -- 1880- -- Correspondence; Chaney, Ralph W. -- 1890-1971 -- Correspondence; Clark, Bruce L. -- 1880- -- Correspondence; Drury, Newton Bishop, -- 1889- -- Correspondence; Eliot, Charles W. -- 1899-1993 -- Correspondence; Hale, George Ellery, -- 1868-1938 -- Correspondence; Hall, Ansel F. -- 1894-1962 -- Correspondence; Hoover, Herbert, -- 1874-1964 -- Correspondence; Howard, Edgar Billings, -- 1887-1943 -- Correspondence; Hughes, Raymond M. -- 1873-1958 -- Correspondence; King, Vernon L. -- Correspondence; Keppel, Frederick P. -- 1875-1943 -- Correspondence; Leland, Waldo Gifford, -- 1879-1966 -- Correspondence; Lillie, Frank Rattray, -- 1870-1947 -- Correspondence; Moulton, Harold Glenn, -- 1883-1965 -- Correspondence; Osborn, Henry Fairfield, -- 1857-1935 -- Correspondence; Packard, Earl L. -- 1885- -- Correspondence; Paton, Stewart, 1865-1942 -- Correspondence; Pearl, Raymond, -- 1879-1940 -- Correspondence; Root, Elihu, -- 1845-1937 -- Correspondence; Rowe, L. S. -- 1871-1946 -- Correspondence; Stock, Chester, -- 1892-1950 -- Correspondence; White, William Charles, -- 1874-1947 -- Correspondence; Wilson, Edwin Bidwell, -- 1879-1964 -- Correspondence; Wright, F. E. -- 1877-1953 -- Correspondence; Yard, Robert Sterling, -- 1861-1945 -- Correspondence; Yerkes, Robert Mearns, -- 1876-1956 -- Correspondence; Carnegie Institution of Washington; National Research Council (U.S.); Smithsonian Institution; Forests and forestry; National parks and reserves; Paleontology; Authors; Educators; Paleontologists